Field-Based Health-Related Physical Fitness Tests in Children and Adolescents: A Systematic Review - Marques, Adilson; Henriques-Neto, Duarte; Peralta, Miguel; Martins, João; Gomes, Fernando; Popovic, Stevo; Masanovic, Bojan; Demetriou, Yolanda; Schlund, Annegret; Ihle, Andreas (Frontiers in Pediatrics, 2021)
Physical fitness (PF) is a multi-component construct and a biomarker of health. Worse PF is related to vulnerability and predicts worse academic achievements. Thus, assessing PF is important to monitor health in youth. This systematic review aimed to identify and inform physical education, health professionals and entities about existing PF batteries and field-tests that can be used in school settings. A comprehensive literature search was carried out in five electronic databases (Academic Search Complete, Education Resources Information Center, PubMed, Scopus, and Web of Science) to identify PF battery protocols that can be carried out in the school setting. Overall, 24 PF batteries were identified. Regarding the PF components assessed, only cardiorespiratory fitness and upper body strength were contemplated in all batteries. Middle-body strength and lower body strength were presented in most batteries (21 and 19 of 24, respectively). Agility (16 of 24) and body composition (16 of 24) were also considered in several batteries, although to a lesser extent. Flexibility (14 of 24) and speed (12 of 24) were the PF components less represented in the batteries. Among the 24 identified PF batteries, 81 PF tests assessing the different PF components were encountered. The advances in the PF field-based assessment in school settings and health in youth resulted in the amplification of the number of existing batteries. Considering the connection between PF and health and the opportunity that the school setting provides to assess fitness in children and adolescents, there is a need for standardization and a consensus of PF assessments in this specific setting.